Students’ Emotional Intelligence, Self-Efficacy, and Schemata in Speaking Performance - Tri Bintang Nusantara; Muhammad Asfah Rahman; Murni Mahmud (Har Press Indonesia, 2021)
The objectives of the research were to find out the level of students’ emotional intelligence, to find out the level of students’ self-efficacy, to find out the level of students’ schemata, to find out there are emotional intelligence, self-efficacy, and schemata simultaneously have significant effect in speaking performance, and to find out which one emotional intelligence, self-efficacy, and schemata has granted contribution in speaking. This study employed mixed method research. The technique of taking sample was volunteer sampling. The population of this research was 35 students of Muhammadiyah University of Makassar. The research data were collected using questionnaire, speaking test, and interview. The data were analyzed by using Likert scale, descriptive statistic, and multiple linear analyses through SPSS 23 version. The result of this research showed that (1) the students of Muhammadiyah University of Makassar have high emotional intelligence. It was proven by mean score 77.40, and it was in 68-83 range score. (2) The students of Muhammadiyah University of Makassar have high self-efficacy. It was proven by mean score 81.57, and it was in 68-83 range score. (3) The students of Muhammadiyah University of Makassar have high schemata. It was proven by mean score 82.89, and it was in 68-83 range score. (4) Emotional intelligence, self-efficacy, and schemata simultaneously have significant effect on students speaking performance as evidenced by F count = (5.851)>F table (2.90). (5) The independent variable that most influences speaking performance in this research is schemata.